Metal decorated polymeric membranes for low trans partial hydrogenation of soybean oil - Singh, Devinder (Kansas State University, 2009)
Multiphase reactions are often constrained by mass transfer limitations which in many cases lead to low reaction rates and undesirable product distribution. Here we fabricate integral-asymmetric polymeric membranes decorated with metal catalysts, to supply hydrogen directly at or near the surface of the catalyst, thus minimizing mass-transfer limitations. The metal decorated polymeric membranes were used for partial hydrogenation of soybean oil with the goal to minimize trans fatty acid (TFA) formation. It was discovered that polymeric membranes with “defective” metal coatings are well suited to achieve low-TFA hydrogenation of soybean oil at quite moderate process conditions. The metal decorated polymeric membranes studied produced significantly lower trans fatty acid as compared to traditional reactors (3.5 wt% at an Iodine Value of 95 as compared to 8 wt% in slurry reactor), at pressures and temperatures which are compatible with the existing systems. The process concept is simpler than some of the alternatives being studied and no catalyst recovery from the oil is needed since the catalyst is immobilized on the membrane. Metal decorated polymeric membranes having a variety of hydrogen fluxes, skin defects, and catalyst loadings were evaluated. All the metal decorated polymeric membranes evaluated produced low TFA. Membranes with high hydrogen fluxes resulted in higher hydrogenation rates but had little influence on TFA formation. Membranes with higher catalyst loadings resulted in lower TFA but increased saturate formation. Metal decorated polymeric membranes behaved differently to changes in temperature and pressures when compared to traditional slurry reactors. They showed a minor increase in TFA with temperature (50-90 °C) as compared to traditional slurry reactors. The hydrogenation rate and cis-trans isomerization also showed a modest dependence on pressure. Due to the defective nature of the metal layer on the polymeric membrane skin and the low temperatures (50-90 °C) at which the reactor is operating, the hydrogen permeability of metals has a minor influence on hydrogenation reaction. A range of metal catalysts can be used for the given system. Repeat runs using the same membrane showed a decrease in hydrogenation activity, without any change in isomerization or hydrogenation selectivity. Initial results indicate the decreased activity may not be from leaching of catalyst from membrane surface nor from sulfur poisoning.
Keywords: membrane reactor; partial hydrogenation; Trans fatty acid; metal decorated polymeric membrane; soybean oil; Engineering, Chemical (0542)